2015
DOI: 10.2174/1389200216666150206124424
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacokinetics, Pharmacodynamics and Safety of Sucroferric Oxyhydroxide

Abstract: Sucroferric oxyhydroxide (VELPHORO®) is a polynuclear iron-based phosphate binder recently approved for the treatment of hyperphosphataemia in patients with chronic kidney disease (CKD). As a number of the available phosphate binders do not provide the optimal combination of good efficacy, adequate tolerability and low pill burden, sucroferric oxyhydroxide constitutes a promising alternative. Among the attributes of an ideal phosphate binder is minimal absorption and, hence, low risk of systemic toxicity. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 67 publications
2
9
0
1
Order By: Relevance
“…Regarding the clinical laboratory tests, increasing trends in serum ferritin, TSAT, and haemoglobin levels were observed in the PA21 group as well as the previous Phase III study . However, the previous non‐clinical and clinical studies of PA21 confirmed that the iron absorption level was consistently low and no iron accumulation was indicated in the previous long‐term study . When comparing the current study and the previous Phase III study, the absolute ferritin values and fluctuation range of ferritin were higher in the previous study.…”
Section: Discussionsupporting
confidence: 50%
“…Regarding the clinical laboratory tests, increasing trends in serum ferritin, TSAT, and haemoglobin levels were observed in the PA21 group as well as the previous Phase III study . However, the previous non‐clinical and clinical studies of PA21 confirmed that the iron absorption level was consistently low and no iron accumulation was indicated in the previous long‐term study . When comparing the current study and the previous Phase III study, the absolute ferritin values and fluctuation range of ferritin were higher in the previous study.…”
Section: Discussionsupporting
confidence: 50%
“…Lanthanum binds phosphate through its trivalent cation [ 13 ]. Recently, iron (e.g., ferric citrate and sucroferric oxyhydroxide) has also proved effective in lowering phosphate by impeding the absorption of phosphate in the stomach without evidence of toxicity [ 14 , 15 ]. The crucial question, however, is the relative impact of these agents on patient-important outcomes, particularly on mortality.…”
Section: Introductionmentioning
confidence: 99%
“…51 With regard to excretion of the drug in preclinical studies, radioactivity was detected only in feces and not in bile or urine. 49 A further important point is that CKD patients often have to take many medications throughout the day and this could expose them to the risk of drug interactions.…”
mentioning
confidence: 99%